Penggunaan Sistem GPS Untuk Keamanan Kendaraan Dengan Kontrol SMS Menggunakan Mikrokontroler Arduino - Agung Yusuf Pratama; Muhammad Ridwan Lubis; Anjar Wanto; Indra Gunawan; Ika Okta Kirana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Motor vehicle theft cases still often occur around us, this happens because there is still a lack of security systems in motorized vehicles that only use ignition keys and key covers, where the weakness of standard security systems like this has been understood by perpetrators of motor vehicle theft. to perform the action. The need for additional security systems is felt to be very necessary, in order to avoid the occurrence of motor vehicle theft. To overcome all this, a motor vehicle security system was created using SMS with an Arduino-based GPS tracking method, to create a GPS Tracker that can control vehicles via SMS (short message service) that can track or assist the vehicle's position using the Arduino Uno GPS (global positioning system). , SIM 800L. If the vehicle is lost, the owner can be tracked only by SMS to the number that has been programmed on the Arduino uno to prevent and make it easier to get back a stolen motor vehicle.